Predictors of low birth weight in antenatal women - Lakshmi S; Rajkumar K (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
Background: Low birth weight is a reflection of the health care infrastructure and human development in a country. Elimination of low birth weight is essential to achieve a greater life expectancy and quality of life. There are several risk factors for low birth weight which range from maternal, nutritional, genetic and other factors. This study was carried out to evaluate the antenatal predictors of low birth weight.  Methods: This cohort study was carried out among 185 antenatal women who presented in first trimester in our hospital. After eliciting history and detailed anthropometric measurement, hemoglobin was estimated to assess the anemia status. The participants were followed up till delivery. The birth weight of the baby was taken immediately after delivery and recorded. Statistical analysis was done by EPI2005 package. Results: Among 185 women studied 48.6% of them were undernourished. There was a significant association between low BMI and low birth weight. Low birth weight was 34% in underweight women while its 18% in normal women after excluding preterm. Height and weight as an individual factor for low birth weight shows negative results. Conclusion: Underweight pregnant women at booking show increased risk of having low birth weight in babies. The BMI at booking in first trimester usually reflects the pre-pregnant BMI as the weight gain in first trimester is less. This study implies a role of improving pre-pregnant nutritional status of mother which in turn implies neonatal outcome.